Health Education and Health Promotion Skills of Health Care Professionals Working in Family Health Centres - Kabasakal, Esma; Kublay, Gulumser (Suamthi Publications, 2017)
Preventable diseases pose a serious problem worldwide. The role of primary healthcare professionals is especially significant in promoting health. Aim: It is aimed to determine the health care professionals working in family health centres have on health education and health promotion skills. Method: The study sample included 144 health care professionals employed in one of 33 family health centres in Ankara Province. The study data were collected using a survey developed on the health education and health promotion skills included in the family medicine specialty education and curriculum from 2008. Results: It was found that 33.3% of the health care professionals had planned to receive health education, and that approximately half of the health care professionals had actively practiced health education and health promotion skills. Considering that time constraints were reported to be the most significant barriers to health promotion, primary health care professionals, most particularly the nurses, should be provided with comprehensive continuing educative training on health promotion and health education skills to foster their professional development. Health promotion and health education trainings shall serve to help them become more active and take on the responsibility of assuming counselling and training roles in health education.
Keywords: Health education; health promotion; family health centre; health professionals